Analysis of Regional Regulation Number year 2015 Implementation on Urban Green Space Management in Mataram City - Dini Ardiantari, Lale; Ichsan, Andi Chairil; Webliana, Kornelia (Journal of Sylva Indonesiana, 2021)
Green open space is an area that has a function as well as a place to grow plants, both those that grow naturally and are planted. One way to improve environmental quality and revitalize urban ecosystems is by managing the Green Open Space. One of the alternatives supporting this effort is to make supportive and applicable policies, laws, and regulations. This research was conducted to examine the implementation of Regional Regulation Number 8 of 2015 regarding Green Open Space Management in Mataram City and to find out planning strategies in optimizing the implementation of applicable policies. The method used in this research is literature study method, interview, and observation. In this study, six criteria are used based on William N. Dunn’s theory to analyze policies and SWOT analysis to determine the appropriate management strategy. The policy implementation analysis results show that the implementation of these regional regulations falls into the "medium" category with a score of 2.13. This indicates that several indicators need to be tightened to optimize policies’ effectiveness, so it is necessary to revise policies to maximize implementation. Several strategies that can be carried out to maximize the role of stakeholders are disseminating information about the content of local regulations that are applied to all related parties, explaining the programs that will be implemented to create a common understanding for all parties as a whole based on the objectives to be achieved, optimizing local regulations which applies to improve coordination in the implementation of green open space management which aims to maximize the role between agencies to create adequate technical personnel, facilities and infrastructure and synchronize the main tasks and functions of each agency in implementing green open space management to maximize their respective roles.